The Application of Durian Rind as a Burning Stimulant of Coal Briquettes - Sanjaya Sanjaya (Masyarakat Peneliti Kayu Indonesia, 2015)
Durian (Durio zibethinus) originally was wild plants from forests of Malaysia, Sumatera, and Borneo. Durian trees cultivated Indonesian society is primarily not for timber, but to produce fruit. At the season of durian, durian rind becomes waste. A tropical plant product which is unfortunate if the durian rind that contains a lot of fiber disposed of as trash, as long as this happens. Has conducted research utilization fiber of durian rind in the field of coal energy. Durian rind fibers can act as a stimulant ignition of coal. Durian rind fibers in various positions with coal and other material added form a briquettes. The position of the fibers has been investigated: briquettes with fiber outer position (1), lower (2), the side (3), the top-down (4), and two quarters (5). Briquettes with durian serat kulit different positions have different speeds and long flame.Keywords: fibre, durian rind, coal ignition, flame speed, long burning